Presidential rhetoric as crime control theater: the case of cybercrime - Marion, Nancy E. (Criminology, criminal justice, law & society, 2018)
Presidents have increasingly made criminal justice a part of their public agenda. Much of their political speech on crime and violence focuses on creating the impression of action, even when none is taken. Moreover, if actions are taken, they are ineffective and do not result in significant policy shifts. When presidents give the impression that they are fighting crime, it is often called crime control theater. This is characterized by the use of mythic narratives, a reliance on moral panic, little public dissent, and the ineffectiveness of the policy itself. While many previous studies have demonstrated the importance of crime control theater regarding different criminal justice topics, none have focused on the emerging problems of cybercrime.The current study examines the patterns and trends in presidential rhetoric on cybercrime using a qualitative content analysis to test the hypothesis that presidents rely on the techniques that comprise crime control theater when discussing cybercrime, in particular, mythic narrative and moral panic. The findings indicate that presidents, on the whole, tend to rely on these elements when discussing cybercrime. In other words, they rely on techniques of crime control theater to allay public fears of cybercrime but at the same time, postponing any significant action.